Competency‐Based Assessment Tool for Pediatric Tracheotomy: International Modified Delphi Consensus. (10th December 2019) - Propst, Evan J.; Wolter, Nikolaus E.; Ishman, Stacey L.; Balakrishnan, Karthik; Deonarain, Ashley R.; Mehta, Deepak; Zalzal, George; Pransky, Seth M.; Roy, Soham; Myer, Charles M.; Torre, Michele; Johnson, Romaine F.; et al.
Abstract : Objectives/Hypothesis: Create a competency‐based assessment tool for pediatric tracheotomy. Study Design: Blinded, modified, Delphi consensus process. Methods: Using the REDCap database, a list of 31 potential items was circulated to 65 expert surgeons who perform pediatric tracheotomy. In the first round, items were rated as "keep" or "remove, " and comments were incorporated. In the second round, experts were asked to rate the importance of each item on a seven‐point Likert scale. Consensus criteria were determined a priori with a goal of 7 to 25 final items. Results: The first round achieved a response rate of 39/65 (60.0%), and returned questionnaires were 99.5% complete. All items were rated as "keep, " and 137 comments were incorporated. In the second round, 30 task‐specific and seven previously validated global rating items were distributed, and the response rate was 44/65 (67.7%), with returned questionnaires being 99.3% complete. Of the Task‐Specific Items, 13 reached consensus, 10 were near consensus, and 7 did not achieve consensus. For the 7 previously validated global rating items, 5 reached consensus and two were near consensus. Conclusions: It is feasible to reach consensus on the important steps involved in pediatric tracheotomy using a modified Delphi consensus process. These items can now be considered to create a competency‐based assessment tool for pediatric tracheotomy. Such a tool will hopefully allow trainees to focus on the important aspects of this procedure and help teaching programs standardize how they evaluate trainees during this procedure. Level of Evidence: 5 Laryngoscope, 130:2700–2707, 2020